Réponses

2013-08-02T12:34:11+02:00

1)   Pour   x  =  2, on a :

 

      AC  =  6(2) + 5

             =  12 + 5

             =   17

 

      BC  =  2(2) + 3

             =  4 + 3

             =  7

 

      AB  =  AC − BC

             =  17 − 7

             =  10

 

2)   Comme   AB  =  AC − BC

 

      alors       AB  =  (6x + 5) − (2x + 3)

                           =  6x + 5 − 2x − 3

                           =  4x + 2

 

 

3)   Pour   x  =  2,   on a donc :

 

      AB  =  4(2) + 2

            =  8 + 2

            =  10

 

     On trouve donc bien la même valeur qu'en 1.